Comparing of the Reaction Time in Substance-Dependent and Non-Dependent Individuals - Mohammad Narimani; Esmaeel Soleimani; Fereshteh Kord A (Drug Control Headquarters, Research and Education Office, 2012)
Aim: The aim of this study was to compare the simple, selective, and discrimination reaction time in substance-dependent and non-dependent individuals. Method: In this causal-comparative study, the population included of 425 males (opium and crystal dependents) who were referred to addiction rehabilitation centers in Tabriz. By random sampling, 16 opium dependents, 16 crystal dependents, and 16 non-dependent individuals with no history of dependency as the compare group were selected. All groups peered in age, and marital status. For gathering data, "Addicts Admit Questionnaire" and laboratory device known as the "Reaction Time Assay" have been used. Results: The results of this study showed that there are significant differences among all groups in simple reaction time, choice reaction time and reaction time to auditory stimuli, but no significant difference in discrimination reaction time and reaction time to visual stimulus observed. Conclusion: The reaction time of substance-dependent groups is slower than non-dependent groups.